Internalisasi Nilai Nilai Pendidikan Islam dalam Kegiatan Minang Sahari di SMP Negeri 13 Padang - Ulil Abshar; Rini Rahman (Lembaga Yasin AlSys, 2026)
Although the integration of Islamic educational values with local wisdom is important in shaping students’ religious character, studies that specifically analyze these values and their internalization process in Minang Sahari activities remain limited. This study aims to describe the Islamic educational values contained in Minang Sahari activities and to analyze their internalization process among students at SMP Negeri 13 Padang. This study employed a qualitative approach with a descriptive research type. The research informants consisted of the principal, Islamic Religious Education teachers, and students. Data were collected through observation, interviews, and documentation, and were then analyzed using data reduction, data display, and conclusion drawing techniques, while data validity was tested through source and technique triangulation. The results showed that Minang Sahari activities contain Islamic educational values that include aqidah, worship, morality, and muamalah. These values are reflected in various activities, such as the use of traditional attire, traditional art performances, the use of the Minangkabau language, and the implementation of customary traditions rich in religious and social meaning. The process of internalizing values was carried out through habituation, role modeling, and direct experience (learning by doing) involving students’ active participation. This activity was proven to be able to shape students’ religious character, such as discipline, responsibility, cooperation, and respect for others. This study concludes that Minang Sahari activities function not only as a means of preserving local culture, but also as an effective medium for instilling Islamic educational values contextually within the school environment.